Efficacy of Laser Capsulotomy in the Treatment of Posterior Capsule Opacification - Syed Imtiaz Ali, Syed Imtiaz Ali (Journal of Rawalpindi Medical College, 2010)
Background: Neodymium – Ytrium – Aluminim – Garnet (Nd:YAG) laser capsulotomy is an effective treatment of posterior capsule opacification , but is not without its attendant risks Methods: In this interventional study, 200 Eyes with posterior capsule opacification (PCO) were subjected to Nd:YAG laser for posterior capsulotomy using ZEIS visualas YAG II plus system, under topical anaesthesia and dilated pupil with tropicamide eye drops with the help of Abraham Capsulotomy YAG Laser Lens. The patients were assessed for early complications after one hour, next day and after one week and the final visual acuity recorded with best correction. Results:Prior to Nd:YAG laser capsulotomy only 7% (14) patients had good best corrected visual acuity (6/18). After one week follow-up there was significant improvement in (73%) patients (122). The overall rate of early complications was 28.7%. Conclusion: The Nd:YAG laser posterior capsulotomy is a safe outdoor procedure with good visual outcome.